Find the product. If the result is negative, enter "-". If the result is positive, enter "+".
-7(- a2 ) 2 ( -b3 )
![Find the product If the result is negative enter If the result is positive enter 7 a2 2 b3 class=](https://us-static.z-dn.net/files/d48/cb94af45477ba8b0351d25fc0d6f745a.png)
Answer:
7 a⁴ b³
Step-by-step explanation:
-7 ( -a²)²( - b ³)
= -7 ( a²)² ( - b³)
= - 7 ( a²)² × b³
= (-7)( a²*² )× b³
= 7 a⁴ b³
Answer:
Solution given:
(-a²)=-a*-a=a²
-b³=-b*-b*-b=-b³
now
-7(-a²)²(-b³)=-7*a⁴*-b³=-7*-1 *a⁴b³=7a⁴b³
the product is 7a⁴b³.
so
enter"+".